This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
6 4 4 x ( 2 6 ) 4 x 2 6 ( 4 x ) ⟹ 6 ( 4 x ) 2 ( 4 x ) 8 x ⟹ x = 5 1 2 3 x + 8 = ( 2 9 ) 3 x + 8 = 2 9 ( 3 x + 8 ) = 9 ( 3 x + 8 ) = 3 ( 3 x + 8 ) = 9 x + 2 4 = − 2 4
6 4 4 x ( 8 2 ) 4 x 8 8 x 8 x 8 x − 9 x − x ⟹ x = 5 1 2 3 x + 8 = ( 8 3 ) 3 x + 8 = 8 9 x + 2 4 [ ( a n ) m = a n m ] = 9 x + 2 4 = 2 4 = 2 4 = − 1 2 4 = − 2 4 .
Relevant wiki: Rules of Exponents
First, we can factor out 512 to get: 6 4 4 x = 6 4 3 x + 8 × 8 3 x + 8 If we divide both sides by 6 4 3 x + 8 , we get: 6 4 x − 8 = 8 3 x + 8 If we realize that 6 4 = 8 2 , then we can distribute the 2 to the x − 8 : 8 2 x − 1 6 = 8 3 x + 8 Using logic, we can get rid of the 8 and solve for the equation: 2 x − 1 6 = 3 x + 8 When we do that, we get the answer of − 2 4 .
Problem Loading...
Note Loading...
Set Loading...
6 4 4 x = 5 1 2 3 x + 8 2 6 ( 4 x ) = 2 9 ( 3 x + 8 ) 6 ( 4 x ) = 9 ( 3 x + 8 ) 2 4 x = 2 7 x + 7 2 − 7 2 = 3 x x = − 2 4